Analysis of Batu City’s carrying capacity for land development and utilization for disaster-mitigation based tourism - Risfandini, Andini; Ulya, Ayu Fitriatul; Imadiddina, Annisa Hamidah; Yulianto, Irwan (Jurnal Pariwisata Pesona, 2025)
Batu City, widely known as the "City of Tourism," faces mounting environmental pressures due to its dependence on tourism and rapid urban development. This study aims to assess land suitability and tourism carrying capacity within a disaster mitigation framework using Cloud-based Web Geographic Information Systems (GIS). The analysis considers multiple spatial and environmental variables, including natural disaster risk, land capability, erosion potential, and drainage suitability. The results indicate that 86% of the city’s land has low natural disaster risk, making it well-suited for eco-tourism and adventure tourism development. Conversely, 14% of the area shows moderate risk levels, underscoring the need for targeted planning and mitigation efforts. These findings highlight the importance of balancing development with environmental safeguards and involving stakeholders in sustainable infrastructure planning. As a practical output, the study supports the development of the SIMAMBA (Information System for Land Capacity and Suitability Distribution Based on Disaster Mitigation), designed to aid policymakers in guiding tourism development that respects ecological, social, and economic limits. In conclusion, the research reinforces the complementary roles of GIS and carrying capacity assessments in promoting sustainable tourism. Their integration offers a strategic pathway to enhance the resilience of Batu City's tourism sector while conserving its natural resources for future generations.